An Old Complication Welcomes Us in the Modern Era: Lingual Hematoma During Thrombolytic Therapy - Aygün, Sevda; Canpolat, Uğur (European Journal of Therapeutics, 2023)
Lingual hematoma is a rare but potentially life-threatening clinical condition. Securing the airway and urgent treatment for underlying reasons are key management steps. We reported a case to illustrate the management of a lingual hematoma after rescue thrombolysis for a ST-segment elevation myocardial infarction (STEMI) patient.